اضطراب الكرب ما بعد الصدمة والعوامل المؤثرة فيه لدى الأيتام السوريين - عبد العال، هدى (Kulliyah of Education, International Islamic University Malaysia, 2018)
PTSD (Post-traumatic stress disorder) is considered one of the most common disorders of war and crisis time. like the war taking plane in Syria in the Middle East. The research aims to determine the level of post-traumatic stress disorder and its factors among the Syrian orphans who live in south of Turkey namely “Ghaziantab, Rihaniyah, Antakya and Karkhan”. The research included 131 orphans (57.3% male and 42.7% female) selected via convenience samplling procedure. The analytical descriptive method was used to answer the research questions. A standardized diagnostic clinical scale, (Davidson scale) was used for data collection. A psychologist team helped the researcher in the collection among orphans. The anlaysis process showed various levels of post-traumatic stress disorder, and there no statistically significant differences between Syrian orphans in PTSD level due the selected demographic variables (gender, age, education program and living style). Therefore, the researcher recommanded for providing continuose psychological programs for the Syrian orphans regadless of demographic differences. Furthermore, the researcher recommends studying other variables related to level of shocks among children such as social and cognitive changes caused by forced displacement, impact of moving away from the mother in the orphanages, level of education supervisor in orphanages, and other variables affectting the level of mental health among Syrian orphans.